A Mother’s Unconditional Love - UMP, PNC
Universiti Malaysia Pahang (UMP)’s 5th Convocation was a joyous and historical moment for its 1,030 graduates. However, it was the most celebrated occassion for Siti Hawa Apandi, 21.